Differences in Maternal Leptin Serum Levels between Normal Pregnancy and Preeclampsia - Yusrawati Yusrawati; Ratna Lestari Habibah; Rizanda Machmud (The Prodia Education and Research Institute (PERI), 2015)
BACKGROUND: Maternal circulating leptin, placental leptin gene expression and protein levels are increased in preeclampsia as compared with those in normal pregnancy. Increased serum leptin levels in preeclampsia which correspond with increased gestational age can be used independently or with other parameters as a marker for the severity of preeclampsia. The advantages of this examination in identifying preeclampsia severity are its simplicity, fast result, low cost and applicability.METHODS: A cross-sectional study was conducted in delivery room, polyclinic of Dr. M. Djamil Hospital, and Biomedical Laboratories of Medical Faculty of Andalas University from December 2013 to April 2014. The samples were collected from 68 women with singleton pregnancy in their third trimester (>28 weeks) presenting to the polyclinic and the delivery room of Dr. M. Djamil hospital. Differences in maternal serum leptin between preeclampsia and normal pregnancy were determined using t-test and Wilcoxon test for data with and without normal distribution, respectively, where p<0.05 indicating a significant results.RESULTS: The mean maternal serum leptin levels in normal pregnancy and preeclampsia were 1588.7964 ± 8.01074 ng/mL and 1608.1725 ± 6.69579 ng/mL, respectively. Thus, there is a statistically significant difference in mean maternal serum leptin levels between the normal pregnancy and preeclampsia (p<0.05).CONCLUSION: There are significant differences in maternal serum leptin levels between women with normal pregnancy and preeclampsia.KEYWORDS: leptin, preeclampsia, pregnancy